A Multicriteria Decision-Making Approach in Exploring the Nexus Between Wind and Solar Energy Generation, Economic Development, Fossil Fuel Consumption, and CO2 Emissions - Rehman, Shazia; Rehman, Erum; Mumtaz, Ayesha; Jianglin, Zhang (Frontiers in Environmental Science, 2022)
Environmental degradation has been identified as a major worldwide concern in recent decades, with CO2 emissions considered as one of the primary drivers of this catastrophe. This study creatively analyzes the underlying impact of wind and solar energy generation, economic development, fossil fuel consumption on CO2 emissions to mitigate the environmental degradation in the world’s top three largest energy consumers and CO2 emitters nations of the world namely, China, India, and the USA. To investigate the integrated impact of CO2 emission, a grey relational analysis (GRA) technique is adopted for the year 1990 to 2017. The Grey technique for order of preference by similarity to ideal solution (G-TOPSIS) technique was employed for further optimization by prioritizing the explanatory factors that have potential influence on CO2 emissions in the selected nations. The outcomes through the GRA technique discovered that India is a major contributor of carbon emission caused by economic development, and China appeared to be the more afflicted nation for raising its carbon emissions owing to fossil fuel consumption. Whereas, the generation of solar and wind energy are grounded factors in the reduction of carbon emissions for China and the USA. In addition, the generation of wind energy showed a considerable impact in the reduction of CO2 emissions, based on the G-TOPSIS analysis. This suggests that reducing CO2 emissions would require a compendious transition from nonrenewable to renewable resources, while the United States and China appear to be on a more promising direction to environmental sustainability than India. As a growing renewable energy pioneer, India should increase the utilization of minimal carbon sources of energy in its electricity grid while limiting its reliance on fossil fuels. The findings of the study potentially aid governments and policymakers in making better decisions and investments to mitigate CO2 emissions while fostering a more environmentally friendly atmosphere.